PERSEPSI MASYARAKAT TERHADAP PENGGABUNGAN KELURAHAN LANDUNG SARI DAN KELURAHAN NOYONTAAN DI KOTA PEKALONGAN - Marolen Silalahi; Susilo Utomo (Journal of Politic and Government Studies, 2017)
Abstract The merger policy villages in Pekalongan, a State government efforts in governing effectively and efficiently. However, on the way the pros and cons of the public arising from the impact of the implementation of the policy, both in administrative issues as well as history. As his case that occurred in the village incorporation Landungsari and Noyontaan in Pekalongan, a conflict people who do not agree with the policies of the Pekalongan government.This study aims to determine the public perception of merging the village Landungsari and Noyontaan in Pekalongan. This study uses a quantitative method with a non-parametric approach. The use of this type of research can be pursued gives an overview of the public perception of the incorporation of the Village in the Landung sari Village and Noyontaan Village, in the implementation of data collection in the field, researchers get 99 respondents using multystage system of random sampling.According to the research found that the majority of the village Noyontaansari not agree with the merger of the villages of Pekalongan City because people Noyontaansari strongly objected to the name of the result of merging the village that did not involve the wider community in policy-making village incorporation. Later in the process can seem abrupt and without their dissemination to the public beforehand. In this case the community, its specialty Noyontaansari society wants the government to restore  their Village to original name, because the name is related to the history of their village.The conclusion that the authors get Noyontaansari Village are society consider merging the Village is not important because before and after unification are not many changes that occurred in the village Government bureaucracies, both in terms of effective and efficient services. Keywords: Policies, Perceptions, Effective, Efficient